Antibacterial Properties of Ten Selected Spices Against Aquaculture Bacteria - Yeo Shin Yi, Jasmine (2015)
The antibacterial effects of ten methanolic spice extracts including black pepper (Piper nigrum Linn.), cinnamon (Cinnamomum zeylanicum BI), clove (Syzgium aromaticum Linn.), cumin (Cuminum cyminum Linn.), star anise (Illicium verum Hook.F.), coriander seed (Coriandrum sativum Linn.), red onion (Allium cepa Linn.), garlic (Allium sativum Linn.), ginger (Zingiber officinale Rose.) and turmeric (Curcuma longa Linn.) were examined by well diffusion method against five cultured bacteria namely, Escherichia coli, Salmonella sp. Pseudomonas aeruginosa, Aeromonas sp. and Streptococcus sp. at the dosage of 200 mg/mL. E.coli was resistant towards all ten spice extracts. Whereas A. Sativum extract has failed to inhibit all five tested bacteria. Z. officinale and C. longa have portrayed positive antibacterial activity towards Aeromonas sp.. Salmonella sp. was only susceptible towards C. zeylanicum, S. aromaticum and I. verum extracts. The minimum inhibitory concentration (MIC) values of S. aromaticum, C. zeylanicum and C. cyminum extracts against present isolated bacteria were range from 0.781 to 12.5 mg/mL at 24th h(s) and 0.098 to 1.563 mg/mL at 48th h(s) respectively. Hence S. aromaticum, C. zeylanicum and C. cyminum have the huge alternative potential of commercial antibiotics for aquaculture uses.